The Potential of South Sumatra Local Wisdom as a Source of Science Learning in Schools to Education Sustainable Development - Elsi Adelia Fitri; Anggie Marsyaelina; Demi Romawina (Postgraduate, University of Mataram, 2026)
Local wisdom is a learning resource that has the potential to support contextual and ethnoscience-based science learning. This research aims to map the concepts of science found in typical foods based on the Musi River and the Lebak Lebung agricultural system in South Sumatra, as well as analyze the needs of prospective teacher students for their use as a source of science learning. The research uses a qualitative descriptive approach supported by quantitative data. Qualitative data was obtained through field observations, interviews, and document analysis, while quantitative data was obtained through needs analysis of 89 prospective teacher students. The results of the study show that both contexts of local wisdom contain the concept of science including heat transfer, changes in the properties of materials due to heating, fermentation, the role of microorganisms, nutritional content, hydrological cycles, characteristics of swampland, adaptation of living things, and environmental conservation. The results of the needs analysis show that most students have sufficient knowledge in both contexts, but still need learning resources that are able to connect local knowledge with science concepts. These findings are the basis for the development of contextual ethnoscience-based science teaching materials to support meaningful learning and continuing education.